Suspected Cystic Fibrosis in Infantile Onset Pneumonias: A Case Series and Review of Literature - Hema Gupta; Parasdeep Kaur; Rajesh Bethu; Priti Priya; Anju Yadav (JCDR Research and Publications Pvt. Ltd., 2022)
Pneumonias are common in infancy and infections remain the most common aetiology especially in developing countries. A case- series of 14 children (9 males and 5 females) with cystic fibrosis is presented who came with persistent/recurrent pneumonia. Most children had infantile onset of symptoms (mean age 4.6±4.2 months). Despite multiple medical consultations in infancy a severe delay in diagnosis (mean age of diagnosis 75.5±65.1 months) and presentation was observed. The youngest child in this series was diagnosed at 2 months of age. Most common manifestations were respiratory, gastrointestinal, and failure to thrive (100%). Sweat chloride test was done in 12/14 children and was elevated in 100%. Genetic mutation was reported in 5 children only. Complications included computed tomography diagnosed bronchiectasis in (7/14;50%), pseudomonas infections (6/14,42.9%; other infections (7/14%, 50%), pulmonary hypertension (3/14,21.4%), gastroesophageal reflux (2/14; 14%). There was a high (5/14,35.7%) mortality in this series, as most of them presented late. Lack of awareness and meager diagnostic facilities are major limitations in early diagnosis of cystic fibrosis and may lead to increased morbidity and mortality among these children.